Different Molecular Methods to Determine Genetic Diversity in Pseudomonas aeruginosa Clinical Isolates - Reem Akram Naji (Journal of Global Pharma Technology, 2020)
A total of (210) clinical specimens were collected from patients suffering from different infections such as burns, wounds, ear infections, diabetic foot, and urinary infections, cultured on differential media. All clinical specimens were cultured on different media. The results indicated that 22 (10 %) of the isolates were belong to P. aeruginosa. It was found that six isolates (27.27%) were isolated from wounds, five isolates (22.72%) from burns, six isolates (27.27%) from ear infections, two isolate (9%) from urine and three isolates (13.63%) from diabetic foot infections. In this study, used RAPD, BOX, and ERIC-PCR for the detection of phylogenetic diversity of pseudomonas aeruginosa isolated from different samples, In general, 18 isolates characterized using the three molecular techniques had comparable number of bands with some degree of polymorphism. P. aeruginosa isolates from the same source were clustered in to different groups. The three molecular techniques generated 2 main clusters, and the results of dendrogram of these techniques reveals that two isolates number(11,12) were similarity 100% in three methods techniques this suggest that this give the more discrimination power. While the pattern of others recorded some difference in the distribution. Keywords: Genotyping, Phenotyping, Pseudomonas aeruginosa, Molecular detection, RAPD, BOX, ERIC.